Legionella pneumophila and Pneumocystis jirovecii Coinfection in an Infant Treated With Adrenocorticotropic Hormone for Infantile Spasm: Case Report and Literature Review. (February 2014) - Musallam, Nadira; Bamberger, Ellen; Srugo, Isaac; Dabbah, Husein; Glikman, Daniel; Zonis, Zeev; Kessel, Aharon; Genizi, Jacob
We describe an 8-month-old infant with infantile spasms treated with adrenocorticotropic hormone (ACTH) who presented with fatal Legionella pneumophila and Pneumocystis jirovecii infection. Emphasis is placed on the ensuing immunosuppression and infectious sequelae of ACTH therapy. Given that ACTH therapy may increase the risk of fatal infection, patients undergoing such treatment should be closely monitored, with particular attention paid to the functioning of the immune system.